Greenland, view of Kjerulf Fjord through to Dicksons Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. In background; N.E. terminal of mts. [mountains] forming north side of Right Valley; here seen turning north. In foreground (below mountains); mouths of streams of Left and Right Valleys. Photo taken from east side of N.W. end of Left Valley, looking N.W. See photos in sequence: 27-1-9; 27-1-8 & 27-1-7. This photo is no. 2 in pan E. Also No. 14 in pan D.